Chlorella pyrenoidosa cultivation in outdoors using the diluted anaerobically digested activated sludge. (December 2015) - Tan, Xiao-Bo; Yang, Li-Bin; Zhang, Ya-Lei; Zhao, Fang-Chao; Chu, Hua-Qiang; Guo, Jun
Highlights: Integration of algal biomass production and wastewater treatment. Successful culture of C. pyrenoidosa in diluted ADAS (using STE) in outdoors. Seasonal changes significantly affected the algal growth and pollutants removal. Abstract: A freshwater green algae Chlorella pyrenoidosa ( C. pyrenoidosa ) was cultured in outdoors using the diluted anaerobically digested activated sludge (ADAS). The outdoors batch culture in every season showed that C. pyrenoidosa can grow normally under natural conditions in the diluted ADAS (STE/ADAS = 1.5/1, 3/1 and 5/1, v/v). Seasonal changes of environmental conditions significantly affected biomass growth and nutrient removal. Optimal biomass growth and nutrient removal was achieved at STE/ADAS = 1.5/1 during summer culture, harvesting a maximum biomass concentration of 1.97 ± 0.21 g/L, average biomass productivity of 291.52 ± 33.74 g/m 3 /day (maximum value of 573.10 ± 41.82) and average lipids productivity of 37.49 ± 5.26 g/m 3 /day (maximum value of 73.70 ± 9.75); simultaneously, the microalgae growth effectively removed nutrients from the wastewater, including 105.6 ± 17.1 mg CODCr /L/day, 36.8 ± 6.1 mg N/L/day and 6.1 ± 1.1 mg P/L/day.